A New Fitness Test of Estimating VO2max in Well-Trained Rowing Athletes - Gao, Wei Dong; Nuuttila, Olli-Pekka; Fang, Hai Bo; Chen, Qian; Chen, Xi (Frontiers in Physiology, 2021)
Background: This study was designed to investigate the validity of maximal oxygen consumption (VO2max) estimation through the Firstbeat fitness test (FFT) method when using submaximal rowing and running programs for well-trained athletes. Methods: Well-trained flatwater rowers (n=45, 19.8 ± 3.0 years, 184 ± 8.7 cm, 76 ± 12.9 kg, 58.7 ± 6.0 mL·kg-1·min-1) and paddlers (n=45, 19.0 ± 2.5 years, 180 ± 7.7 cm, 74 ± 9.4 kg, 59.9 ± 4.8 mL·kg-1·min-1) completed the FFT and maximal graded exercise test (GXT) programs of rowing and running, respectively. The estimated VO2max was calculated using the FFT system, and the measured VO2max was obtained from the GXT programs. Differences between the estimated and measured VO2max values were analyzed to assess the accuracy and agreement of the predictions. Equations from the previous study were also used to predict the VO2max in the submaximal programs to compare the accuracy of prediction with the FFT method. Results: The FFT method was in good agreement with the measured VO2max in both groups based on the intraclass correlation coefficients (>0.8). Additionally, the FFT method had considerable accuracy in VO2max estimation as the mean absolute percentage error (≤5.0%) and mean absolute error (<3.0 mL·kg-1·min-1) were fairly low. Furthermore, the FFT method seemed more accurate in the estimation of VO2max than previously reported equations, especially in the rowing test program. Conclusions: This study revealed that the FFT method provides a considerably accurate estimation of VO2max in well-trained athletes.